Extending extension - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
The self-help group of agricultural extension support agencies, known as the Neuchâtel Initiative, held its annual meeting in its Swiss birthplace in November 2000